2015
DOI: 10.1155/2015/764906
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Cytosolic Ca2+Concentration by Ginsenoside Ro Are Dependent on Phosphorylation of IP3RI and Dephosphorylation of ERK in Human Platelets

Abstract: Intracellular Ca2+ ([Ca2+]i) is platelet aggregation-inducing molecule and is involved in activation of aggregation associated molecules. This study was carried out to understand the Ca2+-antagonistic effect of ginsenoside Ro (G-Ro), an oleanane-type saponin in Panax ginseng. G-Ro, without affecting leakage of lactate dehydrogenase, dose-dependently inhibited thrombin-induced platelet aggregation, and the half maximal inhibitory concentration was approximately 155 μM. G-Ro inhibited strongly thrombin-elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 53 publications
(53 reference statements)
3
15
0
Order By: Relevance
“…The phosphorylation of IP 3 RI is connected to inhibition of [Ca 2+ ] i mobilization by IP 3 , and the phosphorylation of VASP contributes to inhibition of fibrinogen binding to αIIb/β 3 . In a previous report, we found that G-Ro inhibits thrombin-elevated [Ca 2+ ] i mobilization by phosphorylating IP 3 RI in a cAMP-dependent manner [22] . This means that G-Ro may be involved in inhibition of fibrinogen binding to αIIb/β 3 by decreasing [Ca 2+ ] i , and increasing cAMP.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The phosphorylation of IP 3 RI is connected to inhibition of [Ca 2+ ] i mobilization by IP 3 , and the phosphorylation of VASP contributes to inhibition of fibrinogen binding to αIIb/β 3 . In a previous report, we found that G-Ro inhibits thrombin-elevated [Ca 2+ ] i mobilization by phosphorylating IP 3 RI in a cAMP-dependent manner [22] . This means that G-Ro may be involved in inhibition of fibrinogen binding to αIIb/β 3 by decreasing [Ca 2+ ] i , and increasing cAMP.…”
Section: Discussionmentioning
confidence: 88%
“…It is known that p-selectin is released by Ca 2+ , and subsequently interacts with monocyte to trigger inflammation [34] . G-Ro in a Ca 2+ -antagonistic action inhibited thrombin-induced expression of p-selectin [22] , which means that the decrease of Ca 2+ level by G-Ro might involve in inhibition of inflammation by suppressing thrombin-induced p-selectin secretion. This is also evidenced by results that G-Ro had anti-inflammatory activity in vivo and in vitro [35] , [36] .…”
Section: Discussionmentioning
confidence: 92%
“…It was previously shown that phosphorylation of Akt and/or ERK plays a critical role in platelet function,60, 61, 62 and supports thrombus formation 63, 64. Thus, we examined whether e‐cigarettes exert any effect on these 2 markers of platelet activation.…”
Section: Resultsmentioning
confidence: 96%
“…The mechanism of G-Rg3 inhibitory effect on αIIb/ β 3 function was not clear, but our results suggested that this inhibitory effect was attributed cAMP/VASP Ser 157 signaling pathway. Furthermore, it has been reported that antiplatelet compounds, such as Korean red ginseng extract, ginsenoside Rp1 and ginsenoside Ro increase cyclic AMP levels [16][17]20]. These reports also suggest that the inhibitory action of ginseng saponins on platelet activation might be caused by increased cyclic AMP levels.…”
Section: Discussionmentioning
confidence: 94%
“…However, G-Ro and G-Rg3 (20S) exert suppression of human platelet aggregation [9]. Thus, in the present study, I first examined the effect of G-Ro on cyclic AMP concentration in human platelets and verified its cyclic AMPelevating effect [17]. The current study focused on the G-Rg3induced increase in cyclic AMP level.…”
Section: Discussionmentioning
confidence: 95%